Capturing CO2 by Using a Microalgae Culture Recycle Solution. Issue 12 (16th October 2017) - Chen, Pao-Chi; Chou, Po-Han; Lin, Sheng-Zhong; Chen, Hsiao-Wei
Abstract: The capture of CO2 by means of a microalgae culture solution was explored in a continuous bubble‐column scrubber under a constant pH environment. Optimum conditions for a pilot‐scale study were evaluated. With the Taguchi method, a total of sixteen runs were required. Absorption rate, absorption efficiency, overall mass transfer coefficient, and gas‐liquid flow rate ratio were determined by a material balance model and a two‐film model under steady‐state conditions. From the signal‐to‐noise ratio, the sequence of parameters could be stated. Uncontrolled experiments were also performed and empirical equations were discussed. Abstract : The growth of algae requires CO2 as one of the main nutrients, so there is an opportunity to sequester CO2 by using flue gas emissions from industrial sources as the feed for algae cultivation. A microalgae culture recycle solution was successfully reused to capture CO2 in a continuous bubble‐column scrubber under a constant pH environment. Optimum conditions were elaborated.